Design of concreate structures - Nilson, Arthur H. (Mc Graw-Hill, 1997)
This updated student text aims to establish a firm understanding of the behaviour of reinforced concrete structures, and to develop proficiency in the methods used in current structural design practice. Step-by-step design procedures are given to guide the student.